Second Year Winner: Pawmi: An Exploration of Rhetoric in Pokémon Relevance: PRWR 2007, Rhetoric: Strategy and Application. CD: Laura Allen. - MacIsaac, Robert (Jan Rehner Prize for Writing, 2023)
This paper presents a detailed tracing of the rhetorical strategies used by the Pokémon franchise to create and develop “generational mascots” that embody its sensibilities and culture, while conveying clearly defined “branding” elements that distinguish each iteration of game as special and unique, yet connected and relevant to its market. Through a generic participation analysis, the author draws a visual line from the early Pikachu clones to the newly-released Generation 9 Pawmi in a way that reflects the stylistic characteristics of the genre – excited, smiling faces; rounded cheeks and “beady” eyes; translingually pronounceable names – yet diverges from them to convey a less cute, more powerful image that reflects online gaming trends, facilitating brand recognition and growth within a technologically competitive environment.